Indicators of pleasure/pain in hygiene and cleaning outsourced workers of a university hospital - Liana Bohrer Berni; Carmem Lúcia Colomé Beck; Francine Cassol Prestes; Rosângela Marion da Silva; Susan Bublitz; Fabrício Lamb (Universidade Federal do Ceará, 2016)
Objective: to measure the indicators of pleasure and suffering of hygiene and cleaning outsourced workers of a university hospital. Methods: a quantitative study of 51 workers at a university hospital in southern Brazil. A self-administered questionnaire with socio-occupational data and Pleasure Indicators Scale and Suffering at Work were used. There was descriptive and statistical analysis of the internal consistency of the factors using statistical program Predictive Analytics Software. Results: professional achievement and Freedom of expression, were evaluated respectively as satisfactory and critical pleasure indicators. Suffering indicator Lack of recognition was considered bearable and professional exhaustion as critical. Conclusion: the work context researched requires interventions that minimize the suffering of experiences, promote pleasure in work and, consequently, the health of contract workers hygiene and cleanliness.